Digital Transformation of Business for the Purposes of Strategic Development of the Digital Economy - Vladimir Viktorovich DVOEGLAZOV; Irina Alekseevna SBOEVA; Lyudmila Mikhailovna KORNILOVA; Anton Victorovich STEPANOV; Nikolay Nikolaevich PUSHKARENKO; Evgeny Alekseyevich IVANOV; Maria L. TOLSTOVA (Communications of International Proceedings, 2021)
The priority of the national economy is the course towards its accelerated innovative development. In this regard, there is an increased interest on the part of business entities in the use of digital technologies changing the daily life of a person, industrial relations, the structure of economy and education, as well as new requirements for communications, computing capacity, information systems and services arise. Big data is becoming a new asset with alternative value through its use for new purposes and its use for realizing new ideas. In Russia, at present, a topical area of research is the development problems of digital technologies in various fields of activity and related types of economic activity, the generation of new institutions of digital economy. Within the framework of the research, a retrospective analysis of the industrial practices of society was performed, the characteristic features and prevailing technologies of each stage of development were considered. The essence and content of the process of business digital transformation, its organizational and management aspect were researched. A morphological analysis allowing understanding the logic of the process of digital transformation of the economy and business was performed. In the course of research, the key objects of business transformation, the main factors affecting the process of business transformation, are identified, the fundamental approaches and methods of its implementation are characterized. The research shows the differences between the concepts of “digital business”, “digitalization”, “digital transformation”, identifies the types and key features of digital technologies, new challenges and trends in digital transformation of companies in Russia at the current stage of development of the digital economy.
Keywords: Digital Transformation; Digital Economy; Digital Business; Digitalization; Digital Technologies; Business Ecosystem; Business Model.